تلقي المصطلح التعليمي في المعاجم التربوية العربية _ المعجم الموحد لمصطلحات المناهج وطرائق التدريس أنموذجا - بن طناش, عبد الناصر; بوفريوة, هاجر (جامعة الوادي - University of Eloued, 2022)
عرف تاريخ التأليف المعجمي في المجال التربوي العربي معاجم متعددة، تنوعت مناهج وضعها للمصطلحات وآليات ترتيبها وتصنيفها، إلا أن هذا التعدد لا ينفي انطلاق هذه المعاجم من أرضية مشتركة تصبو من خلالها إلى رصد المصطلحات التي تنتمي إلى حقل التربية والتعليم، من بين هذه المعاجم اخترنا المعجم ( الموحد لمصطلحات المناهج وطرائق التدريس ) لاستقراء أهم ما ميز مصطلحات هذا المعجم، الذي سعى فريق العمل من خلاله إلى توحيد المصطلحات التعليمية، وترتيبها بلغات متعددة، واستقبالها في البيئة العربية بأسس تميزها عن غيرها من المصطلحات ضمن المعاجم التربوية. The history of lexicographical authorship in the Arab educational field has known various dictionaries, and there is a variety of approaches to the creation of terms and the mechanisms for their classification and categorization. However, this plurality does not preclude such dictionaries from starting based on a common ground in which to spot terms belonging to the field of education and learning. Among these dictionaries, we have chosen the “ Unified dictionary for curricula and teaching procedure’s terms” in order to extrapolate the main features of this dictionary’s terms, through which the Working Group has sought to standardize educational terms, arrange them in multiple languages and host them in the Arab environment on bases that distinguish them from other terms within the educational dictionaries
مقال
Keywords: المصطلح التعليمي؛ المعاجم التربوية؛ مناهج وطرائق التدريس